Turbofan engine performances from aviation, thermodynamic and environmental perspectives. (1st October 2021) - Balli, Ozgur; Caliskan, Hakan
Abstract: In this paper, JT15D turbofan engine and its main subcomponents are assessed with the aviation, energy, exergy, environmental, and sustainability analyses. In the first stage, the system's specific thrust and specific fuel consumption of the engine are found as 315.9 N s/kg and 15.8 g/kN.s, respectively. Then, system's energetic efficiency is estimated as 21.15% and exergetic efficiency is accounted to be 19.919%. The system's exergetic improvement potential rate, productivity lack ratio and fuel exergy waste ratio are determined as 1573.535 kW, 402.024% and 80.081%, respectively. The ecological and environmental effect factors of the turbofan system are computed to be 5.020 and 4.020, respectively, while the sustainable efficiency factor and exergetic sustainability index rates are found as 1.249 and 0.249, respectively. Finally, among the system parts, the Combustion Chamber (CC) has minimum rates of sustainable efficiency factor, exergetic efficiency and sustainability index, while it has utmost rates of ecological and environmental effect factors, fuel exergy waste ratio, irreversibility and productivity lack ratios. As a general conclusion, the combustion chamber and low pressure compressor components should be optimized for better performance of the system. Highlights: General aviation and energetic performances of a turbofan engine are assessed. Thermodynamic inefficiencies are obtained for engine and its components. Environmental impacts and sustainability levels of turbofan engine are evaluated. Risky components are determined for enhancing thermodynamic performance.